Patency of the Cavernous Sinus After Medial Wall Resection: An Observational Study - Renteria, Axel E.; Fieux, Maxime; Castro, Bruna; Levi, Lirit; Hung, Li-Ting; Azevedo, Alyssa; Lee, Christine K.; Chang, Michael T.; Hwang, Peter H.; Nayak, Jayakar V.; Fischbein, Nancy; Fernandez-Miranda, Juan-Carlos; Patel, Zara M. (Journal of Neurological Surgery Part B: Skull Base, 2025)
The cavernous sinus medial wall (CSMW) is a critical structure that can be resected in cavernous sinus (CS)-invading tumors. Intraoperative venous bleeding is inevitable upon entering the CS and necessitates hemostatic agents use to cease its flow. There is no literature on the fate of CS patency after such hemostasis. This study aims to address that gap.An observational study was conducted between 2018 and 2025, including patients undergoing endoscopic endonasal approach (EEA) with CSMW or transcavernous resection for CS-invading tumors. Pre- and postoperative magnetic resonance imaging (MRI) images were collected and analyzed for CS patency. Postoperative imaging was grouped into three intervals: 0 to 3, 3 to 12, and >12 months. Demographic data were analyzed to identify predictors of CS non-patency.Of the 186 patients included, postoperative CS patency was achieved in 87.1% after 3.72 months. Univariate analysis demonstrated that preoperative CS non-patency (p < 0.001), incomplete gross tumor resection (p = 0.015), meningioma diagnosis (p < 0.001), and previous head and neck radiation increased the postoperative CS non-patency risk. Multivariate analysis identified preoperative CS non-patency as the only independent factor for postoperative CS non-patency (odds ratio = 9.8, p < 0.001). Persistent non-patency at 3 and 12 months increased long-term postoperative CS non-patency risk by 5.86 and 14.7 times, respectively.This is the first study to report that postoperative CS patency is preserved in most cases after EEA requiring CSMW. A strong predictor of postoperative CS non-patency was identified as preoperative CS non-patency. Further studies are warranted to assess if CS non-patency has significant clinical correlations.
Keywords: CS non-patency; medial wall resection; EEA